A slow rebound sponge material formulation and its manufacturing process

CN120158078BActive Publication Date: 2026-10-09DONGGUAN CITY JIAXIN NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510350307.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2026-10-09
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

例如,现有技术中的慢回弹海绵通常存在回弹速度过快、耐久性不足、吸湿性差等问题,导致其在实际应用中无法满足消费者对舒适性和使用寿命的高要求

Benefits of technology

[0039] This invention provides a novel slow-rebound sponge material formulation and its manufacturing process. By optimizing the raw material ratio and modification treatment, the performance of the sponge is significantly improved. Specifically, the combination of modified isocyanate and hyperbranched polyether polyol not only improves the sponge's resilience but also enhances its durability. Simultaneously, the introduction of nanocellulose crystals effectively improves the sponge's mechanical properties and moisture absorption, resulting in a significant improvement in both comfort and lifespan of the final product. Furthermore, the use of Diels-Alder polysiloxane microspheres further enhances the sponge's structural stability, preventing deformation problems during prolonged use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of sponge production, in particular to a slow-rebound sponge material formula and a manufacturing process thereof. The formula of the sponge material comprises the following components: modified isocyanate 40-60 parts; hyperbranched polyether polyol 30-50 parts; nano-cellulose crystal 3-8 parts; Diels-Alder polysiloxane microsphere 2-5 parts; zinc-imidazole composite catalyst 0.8-1.4 parts; delayed amine catalyst 0.4-0.6 parts; supercritical CO2 foaming agent 5-15 parts; and chain extender 1-3 parts. The purpose of the application is to provide a slow-rebound sponge material formula and a manufacturing process thereof. Through optimization of raw material ratio and modification treatment, the performance of the sponge is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sponge production technology, specifically to a slow-rebound sponge material formulation and its manufacturing process. Background Technology

[0002] Slow rebound foam is widely used in furniture, car seats, and sports equipment due to its excellent cushioning and comfort. Traditional slow rebound foam materials are mainly made of polyurethane-based materials, and while their manufacturing process is relatively simple, they have some performance shortcomings. For example, existing slow rebound foams often suffer from excessively fast rebound speed, insufficient durability, and poor moisture absorption, making them unable to meet consumers' high demands for comfort and lifespan in practical applications. Furthermore, traditional manufacturing processes often have high requirements for the selection and proportioning of raw materials and are difficult to mass-produce, limiting their market application. Summary of the Invention

[0003] In order to overcome the shortcomings and deficiencies of the existing technology, the purpose of this invention is to provide a slow rebound sponge material formulation and its manufacturing process, which significantly improves the performance of the sponge by optimizing the raw material ratio and modification treatment.

[0004] This invention is achieved through the following technical solution:

[0005] In a first aspect, the present invention discloses a slow-rebound sponge material formulation, comprising:

[0006] 40-60 parts of modified isocyanate;

[0007] 30-50 parts of hyperbranched polyether polyol;

[0008] 3-8 parts of nano-cellulose crystals;

[0009] 2-5 parts of Diels-Alder polysiloxane microspheres;

[0010] 0.8-1.4 parts of zinc-imidazole composite catalyst;

[0011] 0.4-0.6 parts of delayed amine catalyst;

[0012] 5-15 parts of supercritical CO2 foaming agent;

[0013] Chain extender 1-3 parts.

[0014] In conjunction with the first aspect, the chain extender is further described as a 1,5-naphthyldiamine chain extender.

[0015] Secondly, the present invention discloses a manufacturing process for slow-rebound sponge material, which includes the following steps:

[0016] S1. The raw materials are weighed according to the weight ratio of the formula:

[0017] S2. Take 3-8 parts of nanocellulose crystals and modify them according to the following process:

[0018] Immerse in a chloroform solution containing 5-10 wt% polycaprolactone and sonicate at 50-70°C for 1-3 hours.

[0019] Centrifugation was used to remove ungrafted polycaprolactone;

[0020] Modified nanocellulose with a surface grafting rate of 25-35% was obtained by vacuum drying;

[0021] S3. In a nitrogen-protected reactor, add 30-50 parts of hyperbranched polyether polyol, heat to 40-60℃ and stir continuously, then add the following in sequence:

[0022] 3-8 parts of modified nanocellulose were dispersed at a high speed of 1500-2500 rpm for 25-35 min;

[0023] Mix 2-5 portions of Diels-Alder polysiloxane microspheres at a stirring speed of 450-550 rpm for 10-20 minutes.

[0024] Add 1-3 parts of chain extender and maintain the temperature at 55-65℃ until completely dissolved to form a premixed system;

[0025] S4. Add 40-60 parts of modified isocyanate to another reactor and heat to 35-45℃;

[0026] Add the premixed system obtained in step S3, and control the dropping rate to make the NCO / OH molar ratio exactly 1.05:1;

[0027] Adding 0.8-1.4 parts of zinc-imidazolium composite catalyst and reacting for 1.5-2.5 h yields a prepolymer with a measured viscosity of 8500 mPa·s.

[0028] S5. Cool the prepolymer to 25-35℃, add 0.4-0.6 parts of delayed amine catalyst, stir at 150-250 rpm for 5-10 min, and immediately transfer to a pressure-resistant foaming mold.

[0029] S6. Inject 5-15 parts of supercritical CO2 foaming agent into the mold and maintain for 25-40 minutes.

[0030] Depressurize to 4.9-5.1 MPa at a rate of 1.9-2.1 MPa / min, and depressurize to atmospheric pressure at a rate of 0.25-0.35 MPa / min;

[0031] After depressurization, place the mold in a 75℃ oven for 3 hours to obtain the foamed body;

[0032] S7. Place the foam in a constant humidity chamber and mature for 20-28 hours;

[0033] The target shape is processed using a waterjet cutting system;

[0034] Treat in a hot press at 110-130℃ for 9-11 minutes.

[0035] In conjunction with the second aspect, further, in step S2, the ultrasonic treatment power is 300W and the frequency is 40kHz; the centrifugation speed is 8000rpm and the time is 15min; the vacuum drying temperature is 60℃ and the time is 12h.

[0036] In conjunction with the second aspect, further, in step S3, 0.5 parts of monohydroxy polyether chain terminator need to be added to the premixed system and stirred for 10 minutes to ensure homogeneity.

[0037] In conjunction with the second aspect, further, in step S6, the pressure of the supercritical CO2 foaming agent is 10-15 MPa, and the solubility is 7-10 wt%.

[0038] The beneficial effects of this invention are:

[0039] This invention provides a novel slow-rebound sponge material formulation and its manufacturing process. By optimizing the raw material ratio and modification treatment, the performance of the sponge is significantly improved. Specifically, the combination of modified isocyanate and hyperbranched polyether polyol not only improves the sponge's resilience but also enhances its durability. Simultaneously, the introduction of nanocellulose crystals effectively improves the sponge's mechanical properties and moisture absorption, resulting in a significant improvement in both comfort and lifespan of the final product. Furthermore, the use of Diels-Alder polysiloxane microspheres further enhances the sponge's structural stability, preventing deformation problems during prolonged use. Detailed Implementation

[0040] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention are described in detail below. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0041] Example 1

[0042] A slow-rebound sponge material formulation, comprising the following raw materials by weight:

[0043] 40-60 parts of modified isocyanate;

[0044] 30-50 parts of hyperbranched polyether polyol;

[0045] 3-8 parts of nano-cellulose crystals;

[0046] 2-5 parts of Diels-Alder polysiloxane microspheres;

[0047] 0.8-1.4 parts of zinc-imidazole composite catalyst;

[0048] 0.4-0.6 parts of delayed amine catalyst;

[0049] 5-15 parts of supercritical CO2 foaming agent;

[0050] Chain extender 1-3 parts.

[0051] The modified isocyanate is a trimer compound that incorporates a dynamic thiourethane bond (-NH-C(=O)-S-), with a dynamic bond dissociation activation energy of ≈80kJ / mol (between hydrogen and covalent bonds), achieving room temperature stability / high-temperature reversibility. With an NCO content of 22%, it exhibits moderate reactivity, preventing runaway gelation.

[0052] Its physical properties include a viscosity of 2500 mPa·s (25℃) and low volatility (vapor pressure <0.1 Pa), ensuring processing safety.

[0053] Hyperbranched polyether polyols possess a third-generation hyperbranched structure (functionality 16), with terminal epoxy groups. The high degree of branching provides three-dimensional crosslinking sites, resulting in a storage modulus that is three times higher than that of linear polyols. The epoxy groups react with amine chain extenders to form a rigid aromatic ring structure.

[0054] Its physical properties include a hydroxyl value of 450 mg KOH / g, a viscosity of 8000 mPa·s (40℃), and good compatibility with nanocellulose.

[0055] The nanocellulose crystals are derived from bamboo pulp, consisting of β-1,4-glucan chains with polycaprolactone (PCL) grafted onto the surface.

[0056] With a hydroxyl density of 5.8 mmol / g, it forms a hydrogen bond network with polyether polyols. The PCL chain (Tg≈-60℃) enhances interfacial toughness and inhibits stress cracking.

[0057] Its physical properties include a diameter of 50 nm, an aspect ratio of >50, and an axial tensile strength of 7 GPa (close to that of carbon fiber).

[0058] Diels-Alder polysiloxane microspheres are made of polydimethylsiloxane with furan / maleimide groups grafted onto it. The reaction is reversible at 60℃ (kreversible≈0.01s-1), achieving thermal repair functionality. The siloxane segments reduce surface energy (surface tension 22mN / m), promoting cell stability.

[0059] Its physical properties include a particle size of 1.5 μm and a density of 1.12 g / cm³. 3 It can be uniformly suspended in the prepolymer.

[0060] The zinc-imidazolium composite catalyst is a complex of zinc ions and 2-methylimidazolium, which selectively catalyzes the isocyanate-hydroxyl reaction (k1 / k2>100, inhibiting side reactions).

[0061] Its physical properties include a thermal decomposition temperature of 180℃, which avoids deactivation during the post-curing stage.

[0062] The zinc-imidazolium composite catalyst and the delayed amine catalyst together form a composite catalyst system.

[0063] The physical properties of the supercritical CO2 foaming agent are: critical point 31.1℃ / 7.38MPa, density 0.47g / cm³. 3 (Supercritical state), high diffusion coefficient (10) -7 m 2 ( / s level) ensures rapid penetration into the polymer matrix. Zero surface tension enables the generation of submicron-sized pores (80% smaller pore size compared to pentane foaming).

[0064] In this embodiment, the chain extender is preferably a 1,5-naphthyldiamine chain extender, which has the following chemical characteristics: a rigid planar naphthalene ring structure, a bis-primary amine group (50% less reactive than aliphatic amines), and the ability to form an aromatic urea bond with isocyanate (decomposition temperature >250℃), thereby improving thermal stability. The conjugated structure absorbs mechanical energy (hysteresis loss is reduced by 30%).

[0065] Its physical properties include a melting point of 128℃, requiring heating to dissolve in a polyol system.

[0066] Example 2

[0067] A manufacturing process for a slow-rebound sponge material includes the following steps:

[0068] S1. The raw materials are weighed according to the weight ratio of the formula described in Example 1:

[0069] S2. Take 3-8 parts of nanocellulose crystals and modify them according to the following process:

[0070] Immerse in a chloroform solution containing 5-10 wt% polycaprolactone and sonicate at 50-70°C for 1-3 hours.

[0071] Centrifugation was used to remove ungrafted polycaprolactone;

[0072] Modified nanocellulose with a surface grafting rate of 25-35% was obtained by vacuum drying;

[0073] S3. In a nitrogen-protected reactor, add 30-50 parts of hyperbranched polyether polyol, heat to 40-60℃ and stir continuously, then add the following in sequence:

[0074] 3-8 parts of modified nanocellulose were dispersed at a high speed of 1500-2500 rpm for 25-35 min;

[0075] Mix 2-5 portions of Diels-Alder polysiloxane microspheres at a stirring speed of 450-550 rpm for 10-20 minutes.

[0076] Add 1-3 parts of chain extender and maintain the temperature at 55-65℃ until completely dissolved to form a premixed system;

[0077] S4. Add 40-60 parts of modified isocyanate to another reactor and heat to 35-45℃;

[0078] Add the premixed system obtained in step S3, and control the dropping rate to make the NCO / OH molar ratio exactly 1.05:1;

[0079] Adding 0.8-1.4 parts of zinc-imidazolium composite catalyst and reacting for 1.5-2.5 h yields a prepolymer with a measured viscosity of 8500 mPa·s.

[0080] S5. Cool the prepolymer to 25-35℃, add 0.4-0.6 parts of delayed amine catalyst, stir at 150-250 rpm for 5-10 min, and immediately transfer to a pressure-resistant foaming mold.

[0081] S6. Inject 5-15 parts of supercritical CO2 foaming agent into the mold and maintain for 25-40 minutes.

[0082] Depressurize to 4.9-5.1 MPa at a rate of 1.9-2.1 MPa / min, and depressurize to atmospheric pressure at a rate of 0.25-0.35 MPa / min;

[0083] After depressurization, place the mold in a 75℃ oven for 3 hours to obtain the foamed body;

[0084] S7. Place the foam in a constant humidity chamber and mature for 20-28 hours;

[0085] The target shape is processed using a waterjet cutting system;

[0086] Treat in a hot press at 110-130℃ for 9-11 minutes.

[0087] Example 3

[0088] A manufacturing process for a slow-rebound sponge material includes the following steps:

[0089] S1. The raw materials are weighed according to the weight ratio of the formula described in Example 1:

[0090] S2. Take 5 portions of nanocellulose crystals and modify them according to the following procedure:

[0091] Immerse in a chloroform solution containing 10 wt% polycaprolactone and sonicate at 60°C for 2 hours;

[0092] Centrifugation was used to remove ungrafted polycaprolactone;

[0093] Modified nanocellulose with a surface grafting rate of 30% was obtained by vacuum drying;

[0094] S3. In a nitrogen-protected reactor, add 40 parts of hyperbranched polyether polyol, heat to 50°C and stir continuously, then add the following in sequence:

[0095] Five portions of modified nanocellulose were dispersed at 20,000 rpm for 30 minutes.

[0096] Four portions of Diels-Alder polysiloxane microspheres were mixed at a stirring speed of 500 rpm for 15 minutes.

[0097] Two parts of chain extender, maintained at 50°C until completely dissolved to form a premixed system;

[0098] S4. Add 50 parts of modified isocyanate to another reactor and heat to 40°C;

[0099] Add the premixed system obtained in step S3, and control the dropping rate to make the NCO / OH molar ratio exactly 1.05:1;

[0100] Adding 1 part of zinc-imidazolium composite catalyst and reacting for 2 hours yielded a prepolymer with a measured viscosity of 8500 mPa·s;

[0101] S5. Cool the prepolymer to 30°C, add 0.5 parts of delayed amine catalyst, stir at 200 rpm for 8 minutes, and immediately transfer to a pressure-resistant foaming mold.

[0102] S6. Inject 10 parts of supercritical CO2 foaming agent into the mold and maintain for 30 minutes;

[0103] Depressurize to 5 MPa at a rate of 2 MPa / min, and depressurize to atmospheric pressure at a rate of 0.3 MPa / min;

[0104] After depressurization, place the mold in a 75℃ oven for 3 hours to obtain the foamed body;

[0105] S7. Place the foam in a constant humidity chamber and mature for 25 hours;

[0106] The target shape is processed using a waterjet cutting system;

[0107] Treat in a hot press at 120°C for 10 minutes.

[0108] Example 4

[0109] The performance of the sponge product from Example 2 was tested, and the data are as follows:

[0110] Table 1: Performance Test Items

[0111]

[0112]

[0113] Key data comparison and analysis:

[0114] 1. Indentation hardness and support:

[0115] Example 1: 85N (moderate hardness, suitable for medical protective gear and high-end chairs); Traditional product: 60N (soft, prone to collapse after long-term use);

[0116] Advantages: Hardness increased by 42%, providing enhanced support while maintaining slow rebound characteristics.

[0117] 2. Compression set (durability):

[0118] Example 1: 4.2% (far below the industry requirement of 15%);

[0119] Traditional products: 12.5% ​​(prone to plastic deformation at high temperatures);

[0120] Mechanism: The self-healing ability of the dynamic bond network (thiouric acid ester + DA bond) reduces permanent deformation.

[0121] 3. Rebound time and temperature-sensitive response:

[0122] 25℃ standard environment: 10s (meets the definition of slow rebound);

[0123] 37℃ body temperature environment: 15-18s (extended by 50% to adapt to the body temperature adaptation requirements of medical protective gear);

[0124] Traditional products: No temperature sensitivity, but rebound time fluctuates greatly (±30%) at high temperatures.

[0125] 4. Environmental protection and safety:

[0126] VOC emission: 0.02 mg / m³ 3(Only 13% of the requirements of traditional products, meeting the requirements for baby products);

[0127] Flame retardancy: Self-extinguishing time ≤ 5s (traditional products cannot pass the CAL 117 test);

[0128] Biocompatibility: Grade 0 toxicity (traditional products cause cell inhibition due to amine catalyst residue).

[0129] 5. Fatigue resistance (life prediction):

[0130] Thickness loss after 10,000 compressions: 3% (compared to 15% for conventional products);

[0131] Estimated lifespan: Example 1 can reach 50k cycles (traditional products fail after only 15k cycles).

[0132] Table 2: Summary of Performance Advantages

[0133]

[0134] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A manufacturing process for a slow-rebound sponge material, characterized in that, Includes the following steps: S1. Weigh the raw materials according to the following weight proportions: 40-60 parts modified isocyanate, 30-50 parts hyperbranched polyether polyol, 3-8 parts nanocellulose crystals, 2-5 parts Diels-Alder polysiloxane microspheres, 0.8-1.4 parts zinc-imidazolium composite catalyst, 0.4-0.6 parts delayed amine catalyst, 5-15 parts supercritical CO2 foaming agent, and 1-3 parts chain extender; S2. Take 3-8 parts of nanocellulose crystals and modify them according to the following process: immerse them in a chloroform solution containing 5-10wt% polycaprolactone and sonicate them at 50-70℃ for 1-3 hours. Ungrafted polycaprolactone was removed by centrifugation; modified nanocellulose with a surface grafting rate of 25-35% was obtained by vacuum drying. S3. In a nitrogen-protected reactor, add 30-50 parts of hyperbranched polyether polyol, heat to 40-60℃ and stir continuously, then add in sequence: 3-8 parts of modified nanocellulose, disperse at 1500-2500 rpm for 25-35 min; 2-5 parts of Diels-Alder polysiloxane microspheres, mix at 450-550 rpm for 10-20 min; 1-3 parts of chain extender, maintain the temperature at 55-65℃ until completely dissolved to form a premixed system; S4. Add 40-60 parts of modified isocyanate to another reactor and heat to 35-45℃; add the premixed system obtained in step S3, and control the dropping rate to make the NCO / OH molar ratio accurate to 1.05:1; add 0.8-1.4 parts of zinc-imidazolium composite catalyst, and after reacting for 1.5-2.5h, a prepolymer with a measured viscosity of 8500mPa·s is obtained. S5. Cool the prepolymer to 25-35℃, add 0.4-0.6 parts of delayed amine catalyst, stir at 150-250 rpm for 5-10 min, and immediately transfer to a pressure-resistant foaming mold. S6. Inject 5-15 parts of supercritical CO2 foaming agent into the mold and maintain for 25-40 min; depressurize to 4.9-5.1 MPa at a rate of 1.9-2.1 MPa / min, and then depressurize to atmospheric pressure at a rate of 0.25-0.35 MPa / min; after depressurization, place the mold in a 75℃ oven for 3 hours to obtain the foamed body; S7. Place the foam in a constant humidity chamber and mature for 20-28 hours; process it into the target shape using a water jet cutting system; and treat it in a hot press at 110-130℃ for 9-11 minutes.

2. The manufacturing process of a slow-rebound sponge material according to claim 1, characterized in that, The chain extender is 1,5-naphthyldiamine chain extender.

3. The manufacturing process of a slow-rebound sponge material according to claim 1, characterized in that, In step S2, the ultrasonic treatment power is 300W and the frequency is 40kHz; the centrifugation speed is 8000rpm and the time is 15min; the vacuum drying temperature is 60℃ and the time is 12h.

4. The manufacturing process of a slow-rebound sponge material according to claim 1, characterized in that, In step S3, 0.5 parts of monohydroxy polyether chain terminator need to be added to the premixed system and stirred for 10 minutes to ensure homogeneity.

5. The manufacturing process of a slow-rebound sponge material according to claim 1, characterized in that, In step S6, the supercritical The foaming agent has a pressure of 10-15 MPa and a solubility of 7-10 wt%.

Citation Information

Patent Citations

  • Application of polysiloxane elastomer material in self-repairing material based on Diels-Alder reaction

    CN110092911A

  • Polyurethane sponge with low density and high PPI and preparation method thereof

    CN117777392A

  • High-wear-resistance supercritical foaming TPU material and preparation method thereof

    CN121160070A